WSI Corp and CELP UPM Collaborate to Provide Global Lightning Data for Southeast Asia. - Universiti Putra Malaysia, Bahagian Komunikasi Korporat (2009)
ANDOVER, MA, August 31, 2009 - WSI Corporation (Weather Services International), the global leader in weather information, and the Centre of Excellence on Lightning Protection (CELP) at Universiti Putra Malaysia (UPM) have collaborated to provide detailed lightning detection data for Southeast Asia.